A Case Study On The Merger Of Sanofi-Synthelabo And Aventis - Onn, Yap Kin (2004)
An analysis was conducted on the outcome of a link-up between two major pharmaceutical companies, Aventis and Sanofi-Synthelabo. The objective of this case research is to assess the past four years (2000 -2003) financial ratio of the two companies and determine which company will be in the best position to drive a merger and to determine the possible strength and weakness of the new company.